La Estrella del Tolima Newspaper, 1882-1884. The Last Breath of Radical Liberalism in Neiva (2016)
This study examines La Estrella del Tolima, a radical newspaper edited in Neiva between 1882 and 1884, in the context of the fragmentation of liberalism and the rise of the independent sector. In order to do this, we focus on the division of the Liberal Party and the situation of its radical faction. Afterwards, we explore the position and strategy proposed by the radicals, by means of La Estrella, in order to survive as a political power in the national scene and maintain control of the government in the Sovereign State of Tolima. Methodologically, the article derives in the compilation and analysis of the decimononical press of the Great Tolima region; together with a study of the pamphlets and memoirs of the region, enabling an analysis of La Estrella in the context of the editorial universe of Tolima, that captures its importance for the politics of the time. This study postulates that La Estrella consolidated the last tribune of radical opinion and defense in the State of Tolima, due to the relations between the radicals who ran the newspaper and the government, as well as their political permanence in the State until 1884.